The value of intangibles and diversity on boards looking towards economic future returns: evidence from non-financial iberian business organisations - Lopes, I. T.; Ferraz, D. P. (International Journal of Business Excellence, 2016)
The main objective of the current research is to identify the impact of intellectual resources (recognition and disclosure of information) in business organisations and to examine how diversity on boards, as an embodiment of expertise and knowledge, affects performance. Using information from 125 businesses listed on an Iberian stock exchange, two complimentary models (aggregation and disaggregation) are regressed with the objective of identifying to what extent intangible assets and diversity on boards are sources of effective future economic benefit. The salient conclusions are that intangibles are immaterial factors that drive businesses towards future economic benefits; that focus on intangibles has the potential to drive companies towards a sustainable financial and strategic positioning and enhance economic growth. From a pure accounting perspective, identification and measurement of intangibles can contribute to better decision-making. In spite of the limitations—the range of time under analysis, the intrinsic subjective approach observed in the classification of the information—and the use of the five-score Likert scale, the results attained are considered more reliable than those achieved using a dummy variable. The empirical results provide both an understanding of how internal governance mechanisms tested in aggregate positively affect business performance and offer some explanation as to the relationship between internal governance mechanisms and performance. The research adds value to the current literature by exploring the effects of intangibles and internal governance mechanisms on business performance using data from Spanish and Portuguese non-financial listed business organisations.